Developing an innovative role for a clinical nurse specialist in structural heart disease services. (2nd May 2021) - Connolly, Lauren; Pottle, Alison; Smith, Robert
Abstract : This article explores a new advanced nursing role within interventional cardiology. The role was jointly developed by the lead consultant and clinical nurse specialist, and has received the first official centre of excellence award in the world. As a result, the service will now deliver expert training programmes taught by the consultant team and specialist nurse. This service was created for patients with mitral valve disease. It has a dedicated and structured pathway, with the patient always at the centre of care. This article introduces the role of nurse second operator in complex valvular intervention, which allows the clinical nurse specialist to be fully involved in the entire patient journey from referral to discharge. The author describes how the role was established and the developments that have been made in the first 3 years of the post. The role encompasses both inpatient and outpatient care in a bespoke, nurse-led service, as well as responsibility for maintaining accurate data collection and adherence to the patient pathway throughout the service. This has facilitated a streamlined and tailored service that strives to deliver high-quality, equitable care to patients across the UK. It is hoped that this will encourage other centres to develop such roles for specialist nurses.